The opinions and attitudes of dental school academic staff towards oral healthcare education for older adults. (17th June 2015) - Haresaku, S.; Mariño, R.; Naito, T.; Morgan, M. V.
Abstract: The term 'oral health care for older adults' has various interpretations, and its meaning is not clear among dental school academic staff. Additionally, there are no theoretical or practical stand‐alone courses on oral health care for older adults in Japanese dental schools. To improve oral health care education, we investigated the opinions and attitudes toward oral health care education for older adults among academic staff in dental schools. Data were collected in seven dental schools from May to September 2013 via an online questionnaire survey. Five‐hundred‐fifty‐eight academics (428 male, 130 female) participated (response rate 57%). The average number of years since they had completed a university degree was 20.2 (SD 10.2) years. The majority (Over 90%) of participants perceived that oral health care should be provided in nursing facilities, hospitals, and at home. Its treatments and instructions should include, not only methods of keeping good oral hygiene, but also improvement of oral function such as swallowing training and salivary glands massage. The majority (84.2%) suggested oral health care education should be combined as a one‐credit, stand‐alone course. Findings indicate that dental academics have an understanding the need for a course in oral health care for older adults. Participants supported the need for further development of education in oral health care for older adults' in Japan, as a separate course on its own right. However there were some different views about content by teaching field. The need for a national core program for teaching oral health care education was suggested.